FACTORS RELATED TO BPJS PATIENT SATISFACTION CLASS III - Karimah, Nely (Homes Journal: Hospital Management Studies Journal, 2022)
Background: Quality health services that are customer or patient oriented are the main strategy for health care organizations in Indonesia, in order to continue to exist in the midst of increasingly strong global competition. The quality of health services in hospitals is strongly influenced by the service delivery process. Objective: This study aims to examine the factors associated with patient compliance BPJS Inpatient Class III. The location of this research is BLUD RSUD H. Padjonga Dg. Ngalle Kabupaten Takalar Method: This type of research is a quantitative study using a cross sectional. The sampling technique used random sampling as many as 98 patients. Result: The results of the bivariate study showed that there was a relationship between doctor’s services and patient satisfaction of BPJS Inpatient Class III (p=0.000), the relationship between nursing services and patient satisfaction of BPJS Inpatient Class III (p=0.021), there was a relationship between medical support services with patient satisfaction for BPJS Inpatient Class III (p = 0.001), there is a relationship between administrative services and patient satisfaction for BPJS inpatient Class III (p = 0.001) and there is a relationship between doctor services and patient satisfaction for BPJS inpatient Class III (p = 0.000 ) Suggestion: It is necessary to improve the quality, both the quality of physical facilities, available personnel, medicines and medical equipment including resources.